From Global to Local: Comparative Validation of Quiet Quitting Scales in the Indonesian Workforce - Anggun Sejati; Lussy Dwiutami Wahyuni; Gumgum Gumelar Fajar Rakhman (Dinasti International Journal of Education Management And Social Science, 2025)
Quiet quitting has become increasingly common in today’s work environment and raises serious concerns about declining engagement, reducing productivity, and weakening organizational resilience. In response to this emerging challenge, their validity and cultural applicability outside of their original contexts remain underexamined. This study aimed to evaluate and compare the psychometric properties of three widely cited instruments developed by Karrani et al. (2024), Anand et al. (2023), and Galanis et al. (2023) to determine their conceptual and cultural relevance within the Indonesian workforce. Data were collected from 279 employees across diverse industries in Indonesia. Using both EFA and CFA, alongside internal consistency assessments (Cronbach’s ? and McDonald’s ?), the study found that all three instruments demonstrated acceptable to excellent model fit and high reliability (? > 0.87). These findings suggest that, within the Indonesian context, quiet quitting is more prominently expressed through observable behaviors rather than internal psychological states. Among the three instruments, the scale developed by Karrani et al. showed the most robust psychometric performance. The study underscores the importance of culturally grounded validation and encourages future research to examine the predictive utility of these instruments in relation to organizational outcomes such as job satisfaction, commitment, and employee well-being.